A Novel HGBBDSA-CTI Approach for Subcarrier Allocation in Heterogeneous Network - Hasan M.K.; Ismail A.F.; Islam S.; Hashim W.; Ahmed M.M.; Memon I. (Springer New York LLC, 2023)
Complex networks; Computational complexity; Genetic algorithms; Heterogeneous networks; Mobile telecommunication systems; Multiple access interference; Orthogonal frequency division multiplexing; Particle swarm optimization (PSO); Throughput; Co-tier interferences; Customer premises equipment; Dynamic subcarrier allocations; Heterogeneous Network (HetNet); Orthogonal frequency division multiple access; Resource optimization; Sub-carrier allocation; System performance degradation; Frequency division multiple access